2014
DOI: 10.4236/fns.2014.517186
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Consumption Patterns and Market Demands for Honey in the Kingdom of Saudi Arabia

Abstract: Despite the significant annual consumption of honey in Saudi Arabia, information gaps remain with regard to the marketing and market structure of honey along the value chain. This study analyzed the major factors that influenced the consumption, expenditure patterns, and demand of honey in Saudi Arabia. This study forecasted the near-future expected market demands for honey in Saudi Arabia by collecting and analyzing the primary data using questionnaires. A total of 331 respondents from representative regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 7 publications
4
37
0
2
Order By: Relevance
“…In consumption theory, the most important factor in influencing consumption is income as expressed by Ismaiel et al (2014) and Krueger & Perri (2011). Likewise, the variable of family members and education levels also has a positive sign and significant effect on farmer consumption households which have t-test values respectively of 7.887 and 2.013.…”
Section: Estimation Results Of Consumption Modelmentioning
confidence: 99%
“…In consumption theory, the most important factor in influencing consumption is income as expressed by Ismaiel et al (2014) and Krueger & Perri (2011). Likewise, the variable of family members and education levels also has a positive sign and significant effect on farmer consumption households which have t-test values respectively of 7.887 and 2.013.…”
Section: Estimation Results Of Consumption Modelmentioning
confidence: 99%
“…Some authors (12,16) also concluded that taste, aroma, physical state, and colour had important influence on consumers' choice of honey. In addition to the above parameters, the perceived quality of honey was influenced by its source, brand name, and consumers' confidence in the producers.…”
Section: Results Of Sensory Testmentioning
confidence: 99%
“…5). The crucial role of flavour and taste in honey perception is emphasized in many studies (15,16,32).…”
Section: Tab 1 Results Of Pollen Analysis Of Honey Samplesmentioning
confidence: 99%
“…In a more recent Romanian survey carried out in 2012, 98 % (1421/1449) of respondents reported that they had consumed honey and 88 % (1275/1449) of all respondents agreed that honey would be good for health (Pocol and Bolboacă, 2013). In another survey in Saudi Arabia, 87.3 % (289/331) of respondents claimed that they had used honey because of its medicinal properties (Ismaiel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%